The Paradox of Cessie: Juridical Risks Behind the Euphoria of Non-Performing Asset Purchases - Rijal Ibnu Sani; Suartini Suartini; Ahmad Ahmad; Tri Cahya Indra Permana; Gamal Abdul Nasir (Indonesian Journal of Law and Policy Studies, 2025)
The phenomenon of bank receivables assignment (cessie) in Indonesia is currently experiencing a misleading paradigm shift, whereby this instrument is marketed as if it were a transaction for purchasing discounted property assets. The principal issue addressed in this study is a juridical paradox in the form of public misconception equating the position of the cessionary (assignee of receivables) with that of the direct owner of the secured object, whereas legally cessie merely constitutes the transfer of a claim right (vordering op naam). This research aims to deconstruct the proprietary nature of rights in cessie and to map the legal risks arising from the euphoria surrounding the acquisition of non-performing loans. The method employed is normative juridical research using statutory and conceptual approaches. The findings demonstrate that cessie does not automatically transfer ownership of the asset due to its accessory nature; physical control over the collateral still requires enforcement through mortgage execution procedures or eviction lawsuits, both of which are vulnerable to debtor resistance (derden verzet). The study concludes that the euphoria of purchasing cessie without proper legal risk mitigation will entrap buyers in protracted litigation and high costs. In essence, the buyer does not purchase a â€œhouse,â€ but rather a â€œright to claim,â€ fraught with legal uncertainty.